The Design and Validity of STEM-EDP-gamification Worksheet: Ways to Improve Students' Perception of Their STEM Skills and Motivation - Khoiriyah, Riva; Sukriadi, Sukriadi; Haerani, Rosita Putri Rahmi; Suhartini, Erna; Efwinda, Shelly (Jurnal Pendidikan Matematika dan Sains, 2026)
This article discusses the design and validity of STEM gamification worksheets as a means to improve students' perceptions of skills and motivation in STEM learning. This study encourages student motivation and engagement in STEM learning more engagingly and innovatively. This study uses a mixed-method approach with an Educational Design Research (EDR) approach. The EDR method consists of three phases: the first phase is analysis and exploration, the second phase is design and construction, and the third phase is evaluation and reflection. The STEM gamification worksheet was designed using the EDP (Engineering Design Process) learning model designed for four meetings. The worksheet obtained an average assessment for all aspects, namely the content and feasibility aspects of the STEM gamification-based worksheet product of 89.3% which is included in the "Very Valid" category and can be used in science learning. With an overall Aiken's Test value of 0.845 with a very high interpretation. The worksheet also received suggestions and input from game experts and practitioners for improvement and has been revised. The appearance of the worksheet is very important because it can make students, as users, more motivated and interested in learning. This STEM gamification worksheet is expected to be a breakthrough for the world of education in the future, especially in the application of sustainable development principles, SDGs 4, including innovation in improving STEM, SDGs 11, gamification of innovation and infrastructure with engineering design learning methods, and applying environmentally friendly principles in learning.